Broth Microdilution Susceptibility Testing for Leptospira spp. - Murray, Clinton K. (American Society for Microbiology, 2004)
Leptospirosis in humans has traditionally been treated with penicillin or doxycycline. The choice of therapy offered at the time of initial patient presentation is often empirical, as definitive diagnosis can take weeks. Determining the activity of numerous antimicrobial agents against a wide range of Leptospira serovars may broaden empirical therapeutic options. Various antimicrobials have been shown to be active against a limited number of serovars in in vitro studies, chiefly by the use of broth macrodilution techniques. We developed a broth microdilution technique using the commercially available growth indicator alamarBlue. MICs produced by this technique were compared to MICs and minimal bactericidal concentrations produced by the traditional broth macrodilution technique. The internal validity of our methods was assessed with 11 runs over numerous days with a single isolate of Leptospira interrogans serovar Icterohaemorrhagiae. By either method, the MICs for these internal-validity runs fell within 2 dilutions of each other for more than 90% of antimicrobials. A broader application of these two techniques included 12 serovars (including seven species) of Leptospira and six antimicrobials (penicillin G, doxycycline, chloramphenicol, erythromycin, cefotaxime, and ciprofloxacin). Observed reproducibility fell within 2 dilutions for 99% of the duplicate result sets for the MIC microdilution method, compared to 89% for the MIC macrodilution method. The macrodilution method tended to have a higher MIC at which 90% of the isolates were inhibited (MIC(90)) than did the microdilution method, but the MIC(90)s of both methods were within 2 dilutions of each other for all six drugs. The macrodilution and microdilution techniques produced similar results, with microdilution allowing a faster, more streamlined method of producing MIC results.